2017
DOI: 10.1007/s40615-017-0440-3
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety, Stress, and Trauma Symptoms in African Americans: Negative Affectivity Does Not Explain the Relationship between Microaggressions and Psychopathology

Abstract: Prior research has demonstrated a clear relationship between experiences of racial microaggressions and various indicators of psychological unwellness. One concern with these findings is that the role of negative affectivity, considered a marker of neuroticism, has not been considered. Negative affectivity has previously been correlated to experiences of racial discrimination and psychological unwellness and has been suggested as a cause of the observed relationship between microaggressions and psychopathology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
4

Relationship

4
6

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 55 publications
3
51
1
Order By: Relevance
“…For example, using the Differential Emotions Scale (DES) with older adults, Consedine, Magai, Cohen, and Gillespie (2002) found that Whites had significantly greater negative emotionality than Blacks. Further, our own research found the same relationship between negative affectivity using the Positive and Negative Affectivity Scale (PANAS; Watson, Clark, & Tellegen, 1988): White students showed significantly greater trait negative affectivity than did Black students (Williams, Kanter, & Ching, 2018). We then examined the relationships between frequency of experiencing microaggressions using the RMAS and measures of anxiety (Beck Anxiety Inventory; Beck, Epstein, Brown, & Steer, 1988), stress (General Ethnic Discrimination Scale; Landrine, Klonoff, Corral, Fernandez, & Roesch, 2006), and trauma (Trauma Symptoms of Discrimination Scale; Williams, Printz, & DeLapp, 2018).…”
Section: Microaggressions Exert An Adverse Impact On Mental Healthmentioning
confidence: 57%
“…For example, using the Differential Emotions Scale (DES) with older adults, Consedine, Magai, Cohen, and Gillespie (2002) found that Whites had significantly greater negative emotionality than Blacks. Further, our own research found the same relationship between negative affectivity using the Positive and Negative Affectivity Scale (PANAS; Watson, Clark, & Tellegen, 1988): White students showed significantly greater trait negative affectivity than did Black students (Williams, Kanter, & Ching, 2018). We then examined the relationships between frequency of experiencing microaggressions using the RMAS and measures of anxiety (Beck Anxiety Inventory; Beck, Epstein, Brown, & Steer, 1988), stress (General Ethnic Discrimination Scale; Landrine, Klonoff, Corral, Fernandez, & Roesch, 2006), and trauma (Trauma Symptoms of Discrimination Scale; Williams, Printz, & DeLapp, 2018).…”
Section: Microaggressions Exert An Adverse Impact On Mental Healthmentioning
confidence: 57%
“…Williams reports that for two of these three hierarchical regression analyses, NE measures account for sizeable chunks, but not all, of the variance in the association between perceived racial mistreatment and psychopathology, and perceived microaggressions account for substantial amounts of additional variance (Williams, Kanter, & Ching, 2018). With one exception, these findings actually corroborate what I had hypothesized in my article: NE tends to account for some but not all of the relation between microaggressions and adverse mental-health outcomes.…”
Section: Reliance On Self-report and The Role Of Negative Emotionalitymentioning
confidence: 99%
“…However, certain experiences outside of the Criterion A umbrella can still cause a traumatic reaction and can potentially exacerbate an individual's ability to cope with and recover from conventional Criterion A events (e.g., Williams & Leins, 2016). These non-Criterion A stressors include exposure to racist acts (i.e., racial trauma) and additional forms of oppression based on, or at the intersection(s) with, gender, sexuality, and other stigmatized identities (Chae, Lincoln, & Jackson, 2011;Ching, Lee, Chen, So, & Williams, 2018;Holmes, Facemire, & Da Fonseca, 2016;Pieterse, Carter, Evans, & Walter, 2010;Williams et al, 2014;Williams, Kanter, & Ching, 2018;Williams, Peña, & Mier-Chairez, 2017). For example, sexual/gender minorities of color are at risk of experiencing structural stressors such as homophobia or transphobia in their ethnic communities, as well as racism in the lesbian, gay, bisexual, transgender, queer, intersex, and asexual+ (LGBTQIA+) community (for an intersectional conceptual model, see Ching et al, 2018).…”
Section: Stressors and Ptsd In Marginalized Communitiesmentioning
confidence: 99%